Applications of applied kinesiology in dental practice - Suryakant C. Deogade; Dinesh Naitam; Jaiprakash R. Rathod; Sushant M. Patil (Turkish Journal of Kinesiology, 2016)
Amongst different approaches of complementary and alternative medicines used for treating any type of ailment, applied kinesiology (AK) claims to diagnose illness or select therapy by manual testing muscles for strength and weakness. Applications of AK in dental practice have given a complete assessment, reevaluation and understanding of a patient's general health and wellbeing. AK provides dentists with a wide variety of options for enhancing their diagnostic and therapeutic strategies. The different aspects of structural integration, selection of dental materials, and the equipments used for muscle testing have been described in this article. An overview of literature reveals a positive response by many dental clinicians towards this tool. This article reviews regarding AK and its applications in dental practice.